Effect of replacing Tifton Hay with Guandu Hay on intake, digestibility and ingestive behavior of dairy goats - Priscila Bernardo de Andrade; Erica Beatriz Schultz; Bruno Joaninho de Assis Villar; Ana Caroline Ramos Teles da Silva; Letícia dos Santos Lima; Alhandra Daruiz Moraes; Carlos Elysio Moreira da Fonseca; Luís Carlos Vínhas Ítavo (Acta Scientiarum. Animal Sciences, 2020)
The purpose was to evaluate the effect of replacement of Tifton 85 hay with Guandu hay on the intake, digestibility and ingestive behavior of dairy goats. Five Saanen goats with average milk production of 2.26 ± 0.10 kg d-1, around 123 ± 4 days of lactation were assigned to a 5 x 5 Latin square design. The treatments consisted of five levels of replacement with Guandu: 0, 8.4, 16.8, 25.2, or 36.4 %. We sampled the food offered, leftovers and feces to calculate intake and digestibility, and the ingestive behavior was monitored for 24 hours. Regression analysis was applied with 5% significance. The nutrient intake and the digestibility of dry matter, organic matter and protein decreased linearly with increasing levels of Guandu hay in the diet (p < 0.05). On the other hand, the neutral detergent fiber digestibility increased linearly, without change the water intake and ingestive behavior with replacement levels of Tifton hay with Guandu hay in the diet (p < 0.05). The replacement of up to 36.4% Tifton hay with Guandu hay in the dairy goat diet reduces the intake and digestibility of dry matter, organic matter and protein, and increasesfiber digestibility, without changing the ingestive behavior and water intake.